2010
DOI: 10.1007/s00464-010-0953-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term management of corrosive esophageal stricture with balloon dilation in children

Abstract: Short-segment esophageal strictures, improvement of food intake capacity, and increase in intervals of dilation sessions are good patient indicators. We suggest that esophageal balloon dilatation is a safe and effective method of treatment in caustic esophageal strictures and recommend that balloon dilation program be performed for at least 2 years before deciding that dilation has failed and preferring other treatment modalities which have higher risk of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0
11

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 23 publications
(45 reference statements)
2
47
0
11
Order By: Relevance
“…Compared with bougienage, balloon dilatation seems more effective in terms of reducing the total number and frequency of procedures [1,10,14,16]. In one study, a median of 8.5 bougienages were required, while only a median of two balloon dilatations were needed to achieve the same clinical success rate for children with OA [14].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Compared with bougienage, balloon dilatation seems more effective in terms of reducing the total number and frequency of procedures [1,10,14,16]. In one study, a median of 8.5 bougienages were required, while only a median of two balloon dilatations were needed to achieve the same clinical success rate for children with OA [14].…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies have shown that the rupture rate was related to the aetiology of the stricture [3,9]. Moreover, a long stricture or using an inadequate balloon catheter size is also believed to increase the risk of rupture [10,11]. However, because oesophageal rupture following balloon dilatation is uncommon and only transmural ruptures have been evaluated in most endoscopic dilatations, statistical analysis regarding the risk factors was not performed in most studies [11,12].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Early dilation is not recommended due to the associated high incidence of perforation and associated morbidity. Most clinicians wait three to six weeks after the initial injury before attempting dilation 4 .Perforation occurs in approximately 0.5% of procedures 5 . Some patients with benign esophageal strictures do not achieve acceptable symptom relief despite an intensive dilation schedule and gastroesophageal reflux therapy.…”
Section: Discussionmentioning
confidence: 99%
“…1,7 The incidence of stricture formation, which is the most common late complication, is between 2% and 63% in cases of caustic ingestion. 7,14,15 The late complications of caustic ingestion are closely related to the depth and extent of esophageal or gastric injury, which has an effect on inflammation and collagen deposition. The extent and depth of injury depends on the quantity, concentration, and pH of the causative substance, as well as tissue contact time.…”
Section: Figure 2: a Bmentioning
confidence: 99%